Non-occupational lead and cadmium exposure of adult women in Bangkok, Thailand - Zuo Wen Zhang (2018)
This survey was conducted to examine the extent of the exposure of Bangkok citizens to lead (Pb) and cadmium (Cd), and to evaluate the role of rice as the source of these heavy metals. In practice, 52 non-smoking adult women in an institution in the vicinity of Bangkok, volunteered to offer blood, spot urine, boiled rice and 24-h total food duplicate samples. Samples were wet-ashed, and then analyzed for Pb and Cd by ICP-MS. Geometric means for the levels in blood (Pb-B and Cd-B) and urine (Pb-U and Cd-U as corrected for creatinine concentration), and also for dietary intake (Pb-F and Cd-F) were 32.3 μg/l for Pb-B, 0.41 μg/l for Cd-B, 2.06 μg/g creatinine for Pb-U, 1.40 μg/g creatinine for Cd-U, 15.1 μg/day for Pb-F and 7.1 μg/day for Cd-F. Rice contributed 30% and 4% of dietary Cd and Pb burden, respectively. When compared with the counterpart values obtained in four neighboring cities in southeast Asia (i.e. Nanning, Tainan, Manila, and Kuala Lumpur), dietary Pb burden of the women in Bangkok was middle in the order among the values for the five cities. Pb level in the blood was the lowest of the levels among the five cities and Pb in urine was also among the low group. This apparent discrepancy in the order between Pb-B (i.e. the fifth) and Pb-F (the third) might be attributable to recent reduction of Pb levels in the atmosphere in Bangkok. Regarding Cd exposure, Cd levels in blood and urine as well as dietary Cd burden of Bangkok women were either the lowest or the next lowest among those in the five cities. Copyright (C) 1999 Elsevier Science Ireland Ltd. All rights reserved.